Community Empowerment of PCM Kokap on Sustainable Municipal Waste Management through Black Soldier Fly Farming - Aisyah, Siti Nur; Muhammad Ibnu Rizki (International Journal of Community Service Learning, 2023)
Municipal waste management is one of complicated environmental problems found in many areas of Yogyakarta, including in Kokap, Kulon Progo. In addition, the awareness from local society towards the importance of waste management has not well built yet due to the lack of knowledge on this issue. Therefore, this program was aimed to promote better understanding and technical skill of Pimpinan Cabang Muhammadiyah (PCM) Kokap members regarding black soldier fly-mediated waste management. This community empowerment program involved 15 PCM members (aged ranging from 40-55 years old) and carried out using the experiential learning method through participatory approach. It started with focus group discussion and followed by the trial of BSF farming using municipal waste performed by the members for 40 days. Intensive supervision was provided through WhatsApp Group. Results showed that all PCM members were success in cultivating a complete cycle of BSF. Some of the BSF larvae had been used as feed for poultry and fish. The success of this trial was associated to the high enthusiasm from the members in following the technical guidelines provided virtually. Overall, this program has successfully educated the targeted community marked by the accomplishment of PCM Kokap members in executing the trial of municipal waste management. It also conferred the increased member’s understanding regarding the economic value of BSF products to be alternative source of secondary income. The success of this program could be a pilot project to generate society awareness and capacity for higher responsibility with the municipal wastes produced.